2019
DOI: 10.1159/000507411
|View full text |Cite
|
Sign up to set email alerts
|

NR5A1 Gene Variants: Variable Phenotypes, New Variants, Different Outcomes

Abstract: <i>NR5A1</i> (nuclear receptor subfamily 5 group A member 1) is a transcriptional regulator of adrenal and gonadal development and function. Heterozygous and homozygous <i>NR5A1 </i>mutations have been described in people with 46,XY disorders of sex development (DSD). The clinical, endocrine, and genetic features of four 46,XY subjects with <i>NR5A1</i> genetic variants (2 sisters, 2 boys) from 3 unrelated families are reported. All subjects presented with hypergonadotropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Whereas, a compensated hypergonadotropic hypogonadism with elevated gonadotropin levels but still normal testosterone levels as recently reported by Faienza et al, was found in all patients with available laboratory data, an evident hypergonaodtropic hypogpnadism with decreased testosterone levels was only observed in two patients with female sex assignment [44].…”
Section: Discussionsupporting
confidence: 70%
“…Whereas, a compensated hypergonadotropic hypogonadism with elevated gonadotropin levels but still normal testosterone levels as recently reported by Faienza et al, was found in all patients with available laboratory data, an evident hypergonaodtropic hypogpnadism with decreased testosterone levels was only observed in two patients with female sex assignment [44].…”
Section: Discussionsupporting
confidence: 70%
“…26,27 Previous studies had shown phenotypic variations without any genotype-phenotype correlations. [28][29][30] A study of 30 Chinese children with NR5A1 mutations also demonstrated a wide range of external genitalia and identified p. R87C and p.R313C as the most common mutations in this cohort. In addition, exon 4 is the most frequently affected exon in 40% of the patients.…”
Section: Discussionmentioning
confidence: 89%
“…This description is in line with that of Mönig et al., who studied 10 NR5A1 mutated patients during adolescence and puberty ( 24 ). Other authors also showed an impaired Sertoli cell function with a normal or subnormal Leydig cell function conserved at least until puberty ( 23 , 25 , 27 ).…”
Section: Discussionmentioning
confidence: 91%